Pengaruh Metode Demonstrasi Bercocok Tanam Terhadap Kecerdasan Naturalis Anak Usia 5-6 Tahun di TK Gracia Sustain T.A 2022-2023 - Yudikariang Halawa; Rahmadi Ali (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to determine whether there is an effect of the farming demonstration method on the naturalist intelligence of children aged 5-6 years at tk gracia sustain. This study is a type of research that uses Pre-Exprimental research design in which there are still external variables that influence the shape of the dependent variable. The form of design used is One-Group Pretest-Posttest Design, in this study there is a group that is given treatment, then intends to compare the situation before with after treatment. The subjects of this study were 20 children, consisting of 8 boys and 12 girls. The data collection technique used in this study was an observation sheet of farming activities on children's naturalist intelligence. This study uses quantitative analysis techniques in obtaining data. The data analysis technique uses statistical tests, namely normality tests and hypothesis testing using the t-test. Thitung = 46.1538 > Ttabel = 1.725, and because dk = (n-1) = (20-1) and the real level ɑ = 0.05 so it can be concluded that Thitung> Ttabel (46.1538) > (1.725) thus the hypothesis Ho is rejected and Ha is accepted. So it can be stated that there is a significant effect of the farming demonstration method on the naturalistic intelligence of children aged 5-6 years.